Obstacles To Principal Teaching Supervision - Makhsura, Suri; Agustin, Rini; Marsidin, Sufyarma; Rifma, Rifma; Sulastri, Sulastri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
There are various ways that school principals carry out teaching supervision, both autocratically and democratically. This research aims to see what obstacles there are in school principals' teaching supervision. The method used in this research is the library research method related to journals regarding the teaching supervision of school principals. From the results of the discussion it is known that the obstacles in the principal's teaching supervision involve four factors, namely the principal (time, lack of skills and knowledge, stress and personal characteristics of the principal), teachers (teacher attitudes and motivation), students and equipment and facilities.